A Chelating Resin of EDTA-Type Modified Cross-Linking Polystyrene to Preconcentrate Trace Metals for Seawater Detection. (14th October 2022) - Li, Chao; Duan, Linna; Han, Mingchao; He, Hongwei; Yuan, Mengxiang; Wang, Hairong
Abstract : The determination of trace metals in seawater is an important project of marine environmental monitoring. However, the presence of many alkali metal ions with high concentration, such as sodium ion, seriously interferes with the detection limit and accuracy of atomic absorption spectrometry (AAS, flame/graphite furnace integrated). The conventional chemical methods for the enrichment of trace metals are complex, and low boiling point organic solvents are used. In this paper, a kind of commercial cross-linked polystyrene resin microspheres was chloromethylated and aminated to introduce EDTA-type amino polycarboxylic groups and then loaded in a column as the absorption filler. A set of seawater pretreatment and enrichment devices was designed and assembled. The enriching process and conditions of trace Cu, Zn, Pb, and Cd in standard seawater were studied. 10 g of the modified resin could enrich the equivalent seawater and remove successfully the light metal ions. pH = 5∼9 and 0.2 mL/min of the flow rate were the suitable conditions for preconcentration. The enriched metal ions in the eluent were analyzed on the AAS. Compared with the conventional solvent method, the novel material and enrichment device have high preconcentration efficiency, strong anti-interference ability, and low cost and could be directly applied for routine seawater detection.